Quality of Life after Treatment of Presacral Tumors - Didrikaitė, Gabrielė; Čerkauskaitė, Dovilė; Dulskas, Audrius (Lietuvos chirurgija, 2025)
Background. Presacral tumors are rare and anatomically complex lesions located between the rectum and the sacrum. Due to their often asymptomatic nature, most cases are diagnosed incidentally. Although typically benign, these tumors are surgically removed due to the risk of complications or malignant transformation. Successful treatment depends on the choice of surgical approach and the preservation of sacral nerves, both of which directly impact patients’ quality of life. This article aims to review the classification, diagnosis, treatment of presacral tumors and the impact of surgical decisions on patients’ quality of life. Methods. A literature review was conducted using databases such as PubMed, Scopus, Web of Science and ScienceDirect. The included studies provide an overview of classification, diagnosis, treatment of presacral tumors, the impact of complications on quality of life and possible strategies for managing postoperative complications and improving patient well-being. Results. Presacral tumors are most commonly congenital, originating from remnants of embryonic tissue. The primary treatment modality is surgical resection, with the approach depending on tumor location and size. While minimally invasive techniques help reduce the risk of complications, surgery may still result in urinary, bowel, and sexual dysfunction, particularly when sacral nerves are affected. To mitigate these complications and preserve quality of life, nerve-sparing strategies, rehabilitation, and individualized postoperative care play a crucial role. Conclusions. The success of presacral tumor treatment depends on early diagnosis, appropriate surgical strategy, and effective management of functional complications. To ensure long-term quality of life, it is essential to integrate nerve-preservation principles, apply minimally invasive techniques, and provide specialized rehabilitation.
Keywords: presacral tumors; retrorectal tumors; sacrectomy; chordoma; quality of life